Photodoping and Fast Charge Extraction in Ionic Carbon Nitride Photoanodes. (7th August 2021) - Adler, Christiane; Selim, Shababa; Krivtsov, Igor; Li, Chunyu; Mitoraj, Dariusz; Dietzek, Benjamin; Durrant, James R.; Beranek, Radim
Abstract: Ionic carbon nitrides based on poly(heptazine imides) (PHI) represent a vigorously studied class of materials with possible applications in photocatalysis and energy storage. Herein, for the first time, the photogenerated charge dynamics in highly stable and binder‐free PHI photoanodes using in operando transient photocurrents and spectroelectrochemical photoinduced absorption measurements is studied. It is discovered that light‐induced accumulation of long‐lived trapped electrons within the PHI film leads to effective photodoping of the PHI film, resulting in a significant improvement of photocurrent response due to more efficient electron transport. While photodoping is previously reported for various semiconductors, it has not been shown before for carbon nitride materials. Furthermore, it is found that the extraction kinetics of untrapped electrons are remarkably fast in these PHI photoanodes, with electron extraction times (ms) comparable to those measured for commonly employed metal oxide semiconductors. These results shed light on the excellent performance of PHI photoanodes in alcohol photoreforming, including very negative photocurrent onset, outstanding fill factor, and the possibility to operate under zero‐bias conditions. More generally, the here reported photodoping effect and fast electron extraction in PHI photoanodes establish a strong rationale for the use of PHI films in various applications, such as bias‐free photoelectrochemistry or photobatteries. Abstract : Ionic carbon nitrides based on poly(heptazine imides) (PHI) are intriguing materials with possible applications in photocatalysis and energy storage. In this work, effective photodoping and unusually fast charge extraction times in binder‐free PHI photoanodes are demonstrated. These results establish a strong rationale for the use of PHI films in various applications, such as bias‐free photoelectrochemistry or photobatteries.